(untitled) (The Pakistan Development Review, 2010)
I am thankful to PIDE for giving me the opportunity to be here and participate in this important discussion. It is always exciting to come back to this audience because this is where I started my career as an economist. We have with us Dr S. M. Naseem and Dr Nawab Haider Naqvi who guided me in my earlier years and I would like to thank them also. I will try to restore some balance after Dr Ashfaque’s alarming comments on the state of the economy, recognising well that we have challenges that need to be addressed. Mr Baldridgde in his discussion has given us fifty questions that capture many of the challenges. But first let me say a few words about whether politics should triumph over economics or the other way around. Lets not forget that we have a democratically elected government that represents a delicate coalition of several political parties and competing political interests. In this setting, it is not at all surprising that technocratic economic solutions are secondary to the political ones, and that “economics does not triumph over politics” as lamented by the previous panelist. In a democratic framework, the economists’ role is to ensure that political objectives are met without inflicting an unsustainable fiscal burden and sacrificing the long term development objectives.